Chiroptically-Active Quantum Nanostructures - LOUDON, ALEXANDER (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
In this research, a wide variety of fluorescent nanoparticles have been synthesised and analysed through the lens of optical activity and potential chiroptical applications. Cadmium and cadmium-free fluorescent nanoparticles were synthesised using a range of synthetic approaches including aqueous co-precipitation, hot-injection and heating up techniques. While the majority of the particles analysed in this research were spherical (quantum dots), efforts were taken to produced several different shapes such as nanoplatelets, dot-in-rods and nanotetrapods. Using ligand exchange techniques, and the inclusion of chiral stabilising ligands in the synthesis of these particles, optical activity was induced and subsequently analysed using circular dichroism spectroscopy. The resultant chiral nanoparticles were tested for potential applications in a series of experiments including enantio-cytotoxicity, enantioselective quenching, and enantioselective biological imaging. While producing particles which demonstrated ligand-induced optical activity was the primary focus of this research, many of the tested applications demonstrated clear differences in the behaviour of nanoparticles stabilised with opposite enantiomer ligands.
APPROVED
Keywords: Quantum Dots; Chemistry; Chirality